Formulation and Evaluation of a Traditional Scrub Cream Based on Cocoa Powder (Theobroma cacao L.) and Klanceng Honey - Bazla, Marsya Batrisyia; Hidayah, Nurul; Ambarwati, Neneng Siti Silfi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The purpose of this study was to create and assess the physical quality of a body scrub cream made with stingless bee honey (kelulut honey) and cocoa powder (Theobroma cacao L.) as a natural skincare product. Using a descriptive quantitative approach, this study created four formulations based on varying amounts of stingless bee honey (2.5% and 5%) and cocoa powder (5% and 10%). Organoleptic, homogeneity, pH, spreadability, adhesiveness, viscosity, hedonic, irritation, and stability tests were conducted using the freeze-thaw method for three cycles at 4°C and 40°C. The findings demonstrated that every formulation had pH values within the proper range for skin and satisfied the physical quality standards for body scrub cream preparations. The preliminary irritation test on 10 panelists showed no signs of erythema, itching, burning sensation, or edema during the observation period, while the hedonic test demonstrated good panelist acceptance. Formula F4 exhibited the best characteristics based on the evaluated physical quality parameters and obtained the highest panelist acceptance score.